Bibliotherapy as a tool of personality development - Rajnai, László (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2024)
Reading, and engaging with literary works in general, can be exceptionally significant for an individual’s development and social integration, as reading motivation can be a key factor in lifelong learning. Motivated readers connect more deeply with various texts, show greater persistence, and possess better comprehension and critical thinking skills. In the field of reading pedagogy, there is an increasing emphasis on developing critical reading skills. These skills encourage students to analyze, question, and evaluate the information they read, thus equipping them to navigate a complex and information-rich world. Closely related to the above is the method of developmental bibliotherapy, which utilizes a wide range of texts to help solve everyday problems and facilitate overall progress in our lives. Bibliotherapy sessions use the language of literature, which describes human nature and phenomena in their complete, universal phenomenological sense. This method can assist with various issues, such as processing grief, improving socialization, and enhancing self-actualization. Through it, we can find a balance between individual and communal values and foster self-awareness and social sensitivity. This study outlines the steps of the bibliotherapeutic process and explains how literary works can be used for personal development in response to the challenges of a post-modern society. Books and texts can strengthen an individual’s autonomy and contribute to improving and maintaining long-term mental well-being. The ultimate goal of therapeutic work is for clients to develop their unique life paths through deep self-reflection and self-knowledge, finding meaning in their lives. Under the guidance of a bibliotherapist, clients receive safe boundaries during their personal development work, as the negative contents depicted in literary works are presented as natural parts of life. This buffering effect can make personal issues more relatable and manageable. Texts thus function as tools for identity testing, facilitating vicarious experiences and model learning. The conflicts depicted in the works and their personal parallels serve as therapeutic signposts, appropriately guiding the possibilities for reframing and reparative experiences, thus helping the full integration of all parts of the self. The study also addresses the regulation of therapeutic depth and the conscious management of therapeutic time and perceptual focus. During bibliotherapy sessions, readers can undergo personal development that enables them to become active participants in their own lives, begin rewriting and revising their life stories, and find new meaning in them. This process aids in becoming more conscious not only in relation to ourselves but also in our relationships with others, as the method increases levels of acceptance and empathy.